Sulong Kabataan Design, Pilot Implementation, and Evaluation of a Youth Substance Abuse Prevention Program. - Ochoa, D. P.
Substance abuse prevention is especially important during adolescence given the propensity of young people to take risks during this period. Although prevention programs have been developed and widely evaluated in other countries, they are costly and have not been adapted to the Filipino context. We developed Sulong Kabataan as a community-based life skills program for substance abuse prevention among urban Filipino youth. We discuss the program design process, pilot implementation, and evaluation among 53 adolescents aged 12 to 17 from a low-resource community. The evaluation of the pilot implementation demonstrates the feasibility of the program, especially with close community partnerships. Preliminary evidence for positive impact was shown in participants? life skills and confdence to refuse alcohol. The strengths of the program include the interactive delivery and positive learning climate, as well as facilitators? warmth and competence informed by knowledge of adolescent development. Future directions are discussed for improving the program design and evaluation, and developing training programs for facilitators.